Time to Breathe - Milliken, Aimee (The Hastings Center report, 2014)
As health care providers, we become all too familiar with suppressing our emotions, putting on a brave face, and going through the necessary motions at the bedside. We power through these emotionally charged scenarios day after day, patient after patient. We try to remain serene, to appear calm, and to exude confidence, competence, and professionalism. We deliver life-altering news to devastated families; we sit at dying patients’ bedsides and hold their hands as their hearts stop; we deplete ourselves physically and emotionally when a healthy patient takes a turn for the worse. We skillfully manage the natural process of another person's body decompensating while we hold back our tears, sadness, or sense of defeat. And then we take a deep breath and walk into the next room to see the next patient. We betray our inner turmoil by putting on a smiling face, by focusing on facts, by completing necessary tasks.